2012
DOI: 10.5657/fas.2012.0203
|View full text |Cite
|
Sign up to set email alerts
|

Organic Acid Extraction of Fluoride from Antarctic Krill Euphausia superba

Abstract: The amount of fluoride removed from Antarctic krill via organic acid extraction depends on the extraction time, concentration, extraction volume, and the nature of the acid itself. The fluoride content in Euphausia superba was determined by measuring the concentration of fluoride ion in acidic extracts using an ion-selective electrode. The best results were obtained by adding 50 mL of 0.01 M citric acid to 0.3-0.5 g of krill and extracting for 5 min. Under these conditions, recoveries of fluoride from frozen w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 5 publications
1
11
1
Order By: Relevance
“…Figure 2 shows the changes in fluoride concentration of samples as a function of acid concentration. For all the acids (HCl, acetic acid, citric acid, and lactic acid), defluoridation efficiency increased significantly with increasing acid concentration, especially the acid concentration from 0.02 to 0.1 M, the results were similar to Xie et al (2012). However, based on the slopes of the four curves, it could be seen that with a continuous increase of acid concentration, the defluoridation efficiency was gradually decreased.…”
Section: Resultssupporting
confidence: 85%
See 2 more Smart Citations
“…Figure 2 shows the changes in fluoride concentration of samples as a function of acid concentration. For all the acids (HCl, acetic acid, citric acid, and lactic acid), defluoridation efficiency increased significantly with increasing acid concentration, especially the acid concentration from 0.02 to 0.1 M, the results were similar to Xie et al (2012). However, based on the slopes of the four curves, it could be seen that with a continuous increase of acid concentration, the defluoridation efficiency was gradually decreased.…”
Section: Resultssupporting
confidence: 85%
“…The recovery rate was displayed in Table 2. The data show that the recovery rate of additional fluoride was more than 99.80%, which was acceptable and indicated that the acid digestion could be used for the determination of fluoride in defatted krill powder by‐product (Xie et al, 2012).…”
Section: Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…. 536-2,400 mg/kg , muscle 4.5-570 mg/kg (Soevik and Breakkan, 1979;Adelung et al, 1987;Sands et al, 1998;Moren et al, 2007;Yoshitomi et al, 2007;Xie et al, 2012). FDA 100 mg/kg (FDA, 2012).…”
Section: Rasteiro and Antunes (2005)mentioning
confidence: 99%
“…There is no unified view on existing forms of fluoride in the Antarctic krill at home and abroad. The fluoride content can be determined by ISE ( Frant & Ross 1966;Čápka et al 2004;Xie et al 2012), spectrophotometry (Khalifa & Hafez 1998), gas chromatography (GC) (Chiba et al 1982;Haldimann & Zimmerli 1993), ion chromatography (IC) (Jeyakumar et al 2008;Koch et al 2010;Lefler & Ivey 2011), and high performance liquid chromatography (HPLC) (Lipka et al 2000;Musijowski et al 2010). IC has been chosen in this paper, as it is a rapid, selective, sensitive and preferred method for the determination of a variety of anions at trace and ultra-trace levels (Pereira 1992;Lopez-Ruiz 2000).…”
mentioning
confidence: 99%